Implementation of Open Jackson Queueing Network on Customer Service and Ticket Service at Pasar Senen Train Station Jakarta - Anisa Kisti, Vuji; Supian, Sudradjat; Nahar, Julita (International Journal of Global Operations Research, 2025)
The increase in the number of users of train services causes a buildup in various service facilities, which affects the quality and efficiency of services. This study aims to optimize the service system at Pasar Senen Station by applying the open Jackson queueing network model using the First Come First Serve discipline. The data used includes external arrival times, service times, and cost components at three main facilities: customer service locket, ticket counter locket, and ticket vending machine locket. The results showed that optimal performance was achieved at the ticket counter (M/M/3) and ticket vending machine (M/M/2) with a busy level of 82.14% and 62.66% respectively. Simulation of reducing the number of servers in customer service to two (M/M/2) results in a busy level of 77.95% and lower total costs.